International Transmissions of Inflation Expectations in a Markov Switching Structural VAR Model - Lars Winkelmann; Aleksei Netsunajev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper extends the discussion of international comovements of actual inflation rates to inflation expectations. Financial market expectations about inflation rates in the United States (US) and Euro Area (EA) are modeled in a structural vector autoregression (SVAR). We demonstrate how the heteroscedasticity of the expectations data enables a flexible and data-driven statistical identification of the model. A multi-step procedure is proposed to explore the economic nature and geographical source of structural shocks. We emphasize the SVAR s ability to derive shocks that disentangle US specific, EA specific and global components. Our main empirical finding indicates that so-called global inflation translates to short horizon inflation expectations. In contrast, long expectations horizons are mostly driven by domestic shocks, thus, appear rather local. Results support the view of credible monetary policy strategies that anchor inflation expectations.
Keywords: E31; F42; E52; 330